Development of Finite Element Field Solver in Gyrokinetic Toroidal Code (Communications in Computational Physics, 2018)
A new finite element (FE) field solver has been implemented in the gyrokinetictoroidal code (GTC) in attempt to extend the simulation domain to magnetic axisand beyond the last closed flux surface, which will enhance the capability the GTCcode since the original finite difference (FD) solver will lose its capability in such circumstances.A method of manufactured solution is employed in the unit fidelity testfor the new FE field solver, which is then further verified through integrated tests withthree typical physical cases for the comparison between the new FE field solver andthe original finite difference field solver. The results by the newly implemented FEfield solver are in great accord with the original solver.